Five-element music therapy based on emotion classification to improve sleep in patients with cancer-related depression: a multi-group randomized controlled trial - Wang, Wenjun; Sheng, Yudong; Xie, Hongmei; Zhao, Jingtao; Zhao, Yang; Zhou, Rui; Zhao, Nan; Wu, Yu (Frontiers in Psychiatry, 2025)
BackgroundSleep disorders are very prevalent in cancer-related depression (CRD) patients, which seriously impacts their quality of life. But the curative effect of drugs is not ideal. Existing five-element music therapy (FEMT) is effective in improving sleep and emotion in cancer patients, but lacks attention to matching the patient’s subjective emotion to the music. In this study, we propose the innovative “FEMT based on emotion classification”, aiming to validate its effect on improving sleep and emotion in CRD patients, and to compare its efficacy with that of traditional FEMT.Methods120 CRD patients were randomly divided into the emotional classification music group (ECMG), the traditional music group (TMG), and the no music group (NMG). The outcome index was the difference between the Pittsburgh Sleep Quality Index (PSQI), Hamilton Depression Scale (HAMD), and Hamilton Anxiety Scale (HAMA) on the 14th and 28th days and baseline. the exploratory indexes were 5-HT, IL-1 β, IL-2, and TNF-α.ResultsBoth ECMG and TMG significantly improved the total score of PSQI, HAMD, and HAMA. ECMG significantly improved sleep disorder on the 14th day, and improved both sleep disorder and daytime dysfunction on the 28th day.TMG improved overall sleep quality and daytime dysfunction on the 28th day.ConclusionBoth therapies can effectively improve sleep disorders and negative emotions in patients with CRD. The former takes effect faster, while the latter has a more stable curative effect. The two therapies can be used as clinical adjuvant treatment, and personalized intervention programs can be selected according to patients’ needs.Clinical trial registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2200062181.